Preparation method of plugging type filtrate reducer for high-temperature drilling fluid

By conducting hydrothermal carbonization reaction between biomass and nano-inorganic particles and combining other additives, an ultra-high temperature micro-nano sealing and filtration reduction agent for high-temperature drilling fluid was prepared, which solved the temperature resistance and environmental protection in the prior art. The problem of insufficient results has achieved the effect of efficiently controlling the loss of drilling fluid.

CN119307240APending Publication Date: 2025-01-14CHINA NAT PETROLEUM CORP +1

Patent Information

Application Number
CN202310867294.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the prior art, the sealing type filter reduction agent used in high-temperature drilling fluid has insufficient temperature resistance and environmental protection, and it is difficult to effectively control the filter loss in deep drilling, and traditional methods do not consider environmental protection.

Method used

By mixing biomass with water, adding nanoinorganic particles and carrying out hydrothermal carbonization reaction, an ultra-high temperature micro-nano sealing and filtration reduction agent is prepared, combining sodium hydroxide, zwitterionic polymer coating agent, and shale Inhibitors and sulfonate copolymers form water-based drilling fluids to improve temperature resistance and environmental protection.

Benefits of technology

It has achieved effective control of the filtration loss of drilling fluid at high temperatures, with temperature resistance up to 220℃, a reduction rate of filtration loss as high as 60%, and a wide range of raw materials, low cost and good environmental protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307240A_ABST
    Figure CN119307240A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a plugging type filtrate reducer used in a high-temperature drilling fluid, and the method comprises the following steps: carrying out first mixing on biomass and water to obtain a first suspension; carrying out second mixing on the first suspension liquid and nano inorganic particles to obtain a second suspension liquid; carrying out hydrothermal carbonization reaction on the second suspension to obtain a first reaction product; and cleaning, drying and crushing the first reaction product to obtain the filtrate reducer. Compared with the traditional filtrate reducer, the ultrahigh-temperature micro-nano plugging filtrate reducer for the water-based drilling fluid provided by the invention cannot be degraded and damaged at high temperature, and the filter loss of the drilling fluid before and after ultrahigh-temperature action is effectively controlled. The high-temperature-resistant fluid loss additive has excellent fluid loss control performance at high temperature, can effectively control the fluid loss additive of the water-based drilling fluid, can resist the temperature of 220 DEG C, and has the fluid loss reduction rate of 60%. Meanwhile, the raw materials are wide in source, low in cost and good in environmental protection performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemistry, and in particular to a preparation method of a plugging type fluid loss reducer used in high-temperature drilling fluid and a water-based drilling fluid. Background Art

[0002] As global oil demand continues to increase, oil and gas exploration and development are gradually developing towards deeper layers. During the drilling process of deep and ultra-deep oil and gas resources, the probability of encountering ultra-high temperature and high pressure formations increases significantly, posing a great challenge to the maintenance of drilling fluid performance. The control of drilling fluid loss during deep and ultra-deep well drilling has always been one of the technical difficulties in drilling engineering. The addition of high-performance fluid loss reducers can optimize the particle size distribution of clay particles, stabilize the drilling fluid colloid, improve the quality of the mud cake, make it dense, tough and thin, thereby reducing the permeability of the well wall, improving the stability of clay particles under complex geological conditions, and achieving the effect of reducing drilling fluid loss.

[0003] Drilling fluid loss reducers are mainly divided into two categories: solid particulate materials and water-soluble polymer materials. Among them, solid particulates mainly include bentonite, asphalt powder, quartz powder, volcanic ash, diatomaceous earth, talcum powder, thermoplastic resin particles and emulsified polymer particles. Water-soluble polymer loss reducers are widely used and come in a wide variety of varieties. They can be divided into the following three categories: natural or modified polymer compounds, modified phenolic resins and polymers. Among them, natural or modified polymer compounds mainly include humic acid, cellulose, lignin, starch and their modified products; modified phenolic resins are based on phenolic resins and are prepared by copolymerization, sulfonation and other reactions with different compounds or polymers; polymer loss reducers use common acrylamide, 2-acrylamide-2-methylpropanesulfonic acid and other monomers as the main monomers, and are copolymerized with other functional monomers containing double bonds to prepare binary or higher polymers.

[0004] At present, the plugging type fluid loss reducers that are widely used mainly include asphalt (powder), super calcium carbonate (powder) and various nanomaterials. However, the use of asphalt (powder) fluid loss reducers is significantly restricted by the softening point temperature, which generally does not exceed 150°C. Super calcium carbonate (powder) raw materials are widely available, but have poor deformation ability in the formation, limited ability to plug microcracks, and the density of the formed filter cake is poor. At present, there are still few plugging type fluid loss reducers that can be used in high-temperature drilling fluids.

[0005] Although there are reports of plugging-type fluid loss reducers that can be used in high-temperature drilling fluids in China, they are usually not heat-resistant or have poor environmental protection. For example, CN116143966A discloses a temperature-resistant and salt-resistant fluid loss reducer that is copolymerized by block polymerization using N,N-dimethyldiallylammonium chloride and sodium p-styrenesulfonate as raw materials, and has a temperature resistance of up to 200°C, but no environmental protection is described; CN116082570A discloses a nano-composite fluid loss reducer that is synthesized by soap-free emulsion polymerization of styrene, methyl methacrylate, acrylamide, dimethyldiallylammonium chloride, and 2-acrylamido-2-methylpropanesulfonic acid, and has a temperature resistance of up to 240°C, but the raw material composition is very complex, and no environmental protection is described; it can be seen that the high-temperature resistant fluid loss reducers currently disclosed in the application mainly focus on improving the high-temperature resistance, and often ignore the consideration of environmental protection, which has certain limitations for the promotion and application in the field of drilling fluids.

[0006] Therefore, preparing a filtrate reducer that is not only resistant to high temperatures but also environmentally friendly has become an urgent problem to be solved. Summary of the invention

[0007] The object of the present invention is to provide a method for preparing a plugging type fluid loss reducer for high temperature drilling fluid, so as to solve the above technical problems.

[0008] To achieve the above object, the present invention provides a method for preparing a plugging type fluid loss reducer for high temperature drilling fluid, the method comprising:

[0009] The biomass is first mixed with water to obtain a first suspension;

[0010] performing a second mixing of the first suspension and the nano inorganic particles to obtain a second suspension;

[0011] performing a hydrothermal carbonization reaction on the second suspension to obtain a first reaction product;

[0012] The first reaction product is washed, dried, and crushed to obtain the fluid loss reducer.

[0013] Optionally, the method further comprises: performing a third mixing of the second suspension and a sulfonic acid group-containing monomer to obtain a third suspension;

[0014] Accordingly,

[0015] subjecting the third suspension to a hydrothermal carbonization reaction to obtain a second reaction product;

[0016] The second reaction product is washed, dried, and crushed to obtain the fluid loss reducer.

[0017] Optionally, the biomass includes one or more of glucose, sucrose, fructose, xylose, starch, cellulose, hemicellulose, and lignin.

[0018] Optionally, the sulfonic acid group-containing monomer includes: 2-acrylamide-2-methylpropanesulfonic acid.

[0019] Optionally, the nano inorganic particles include: nano silicon dioxide, and the particle size of the nano silicon dioxide ranges from 800 to 8000 meshes.

[0020] Optionally, the dosage of the nano inorganic particles is 1.5-15g.

[0021] Optionally, the mass ratio of the biomass to the nano-inorganic particles is (1-8):1.

[0022] Optionally, the first mixing conditions include: temperature of 10-40° C., stirring rate of 2000-12000 rpm, and time of 5-60 min.

[0023] Optionally, the second mixing conditions include: temperature of 10-40°C, stirring rate of 2000-12000 rpm, and time of 5-60 min.

[0024] Optionally, the conditions of the hydrothermal carbonization reaction include: temperature of 150-300° C. and time of 8-48 h.

[0025] Optionally, the hydrothermal carbonization reaction is carried out in a polytetrafluoroethylene sealed tank.

[0026] Optionally, the ratio of the volume of the second suspension or the third suspension to the volume of the polytetrafluoroethylene sealed tank is ≧50%.

[0027] The present invention also provides a water-based drilling fluid, comprising: a plugging type fluid loss reducer for high-temperature drilling fluid, sodium hydroxide, a zwitterionic polymer coating agent, a shale inhibitor, white oil and a sulfonate copolymer fluid loss reducer.

[0028] Optionally, the mass percentage of the plugging-type fluid loss reducer used in high-temperature drilling fluid is 0.1-5%, the mass percentage of the sodium hydroxide is 0.1%-0.3%, the mass percentage of the zwitterionic polymer coating agent is 0.1%-0.5%, the mass percentage of the shale inhibitor is 1%-3%, the mass percentage of the white oil is 1%-3%, and the mass percentage of the sulfonate copolymer fluid loss reducer is 0.1%-0.5%.

[0029] Technical effects and advantages of the present invention:

[0030] The invention provides a preparation method of a plugging type fluid loss reducer for high-temperature drilling fluid, the method comprising: first mixing biomass with water to obtain a first suspension; second mixing the first suspension with nano inorganic particles to obtain a second suspension; performing a hydrothermal carbonization reaction on the second suspension to obtain a first reaction product; and washing, drying and pulverizing the first reaction product to obtain the fluid loss reducer.

[0031] Compared with traditional fluid loss reducers, the ultra-high temperature micro-nano plugging fluid loss reducer for water-based drilling fluid provided by the present invention will not degrade and be damaged at high temperatures, and can effectively control the fluid loss of drilling fluid before and after ultra-high temperature action. It also has excellent fluid loss control performance at high temperatures, can effectively control the fluid loss reducer of water-based drilling fluid, has a temperature resistance of up to 220°C, and a fluid loss reduction rate of up to 60%. At the same time, the raw material source is wide, the cost is low, and the environmental protection performance is good.

[0032] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention is a flow chart of a method for preparing a plugging type fluid loss reducer for use in high temperature drilling fluid. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings provided by the present invention, and the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0035] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportion relationship or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.

[0036] In order to solve the deficiencies of the prior art, the present invention discloses a method for preparing a plugging type fluid loss reducer for high temperature drilling fluid, such as Figure 1 The method comprises:

[0037] (1) mixing the biomass with water to obtain a first suspension;

[0038] (2) performing a second mixing of the first suspension and the nano inorganic particles to obtain a second suspension;

[0039] (3) performing a hydrothermal carbonization reaction on the second suspension to obtain a first reaction product;

[0040] (4) The first reaction product is washed, dried, and crushed to obtain the fluid loss reducer.

[0041] It should be noted that the mixing process may further include the following steps: after the first suspension is mixed with the inorganic nanoparticles for a second time, it is mixed with the sulfonic acid group-containing monomer for a third time to obtain the suspension (third suspension).

[0042] Wherein, the third suspension contains: biomass, water, nano inorganic particles and optional sulfonic acid group-containing monomers.

[0043] It should also be noted that the above biomass is selected from one or more of glucose, sucrose, fructose, xylose, starch, cellulose, hemicellulose, and lignin, preferably one or more of glucose, xylose, starch, cellulose, hemicellulose, and lignin.

[0044] It should also be noted that the above-mentioned nano inorganic particles are nano silicon dioxide, and the particle size of the nano silicon dioxide ranges from 800 mesh to 8000 mesh. The dosage of the above-mentioned nano inorganic particles is 1.5-15g, preferably 5-10g.

[0045] It should also be noted that the mass ratio of the above-mentioned biomass to the nano inorganic particles is (1-8):1, preferably (1-4):1.

[0046] It should also be noted that the types of the above-mentioned sulfonic acid group-containing monomers are conventionally selected in the art. Preferably, the sulfonic acid group-containing monomer is 2-acrylamide-2-methylpropanesulfonic acid.

[0047] It should also be noted that the above-mentioned first mixing conditions include: temperature of 10-40°C, preferably 20-40°C; stirring rate of 2000-12000 rpm, preferably 6000-10000 rpm; time of 5-60 min, preferably 30-60 min.

[0048] It should also be noted that the above-mentioned second mixing conditions include: temperature of 10-40°C, preferably 20-40°C; stirring rate of 2000-12000 rpm, preferably 6000-10000 rpm; time of 5-60 min, preferably 30-60 min.

[0049] It should also be noted that the conditions of the hydrothermal carbonization reaction include: a temperature of 150-300°C, preferably 180-260°C; a time of 8-48h, preferably 12-36h. When the biomass used is glucose, sucrose, fructose, xylose, starch and hemicellulose, the temperature of the hydrothermal carbonization reaction should be greater than or equal to 180°C; when the biomass used is cellulose, the reaction temperature should be greater than or equal to 220°C; when the biomass used is lignin, the reaction temperature should be greater than or equal to 230°C.

[0050] It should also be noted that the hydrothermal carbonization reaction can be carried out in a conventional reaction vessel in the art. Preferably, the hydrothermal carbonization reaction is carried out in a closed reaction vessel, such as a polytetrafluoroethylene closed tank.

[0051] It should also be noted that the volume ratio of the second or third suspension to the volume of the reaction container is greater than or equal to 50%, preferably greater than or equal to 80%. That is, when the volume of the reaction container is 100 mL, the volume of the added suspension should be greater than or equal to 80 mL.

[0052] It should also be noted that the above-mentioned washing and drying conditions are not particularly limited. Preferably, the washing conditions include: centrifuging the reaction product at 80,000 rpm for 10-20 min to obtain a solid product, and washing the product with deionized water and / or anhydrous ethanol at least three times. The drying conditions include: drying at a temperature of 60-100°C.

[0053] The present invention also provides a water-based drilling fluid, comprising: a plugging type fluid loss reducer for high-temperature drilling fluid, sodium hydroxide, a zwitterionic polymer coating agent, a shale inhibitor, white oil and a sulfonate copolymer fluid loss reducer.

[0054] It should be noted that, based on the total weight of the water-based drilling fluid, the content of sodium hydroxide is 0.1%-0.3%; the content of the zwitterionic polymer coating agent is 0.1%-0.5%; the content of the sulfonate copolymer fluid loss reducer is 0.1%-0.5%; the content of the shale inhibitor is 1%-3%; the content of the white oil is 1%-3%; the dosage of the above-mentioned ultra-high temperature micro-nano plugging fluid loss reducer is 0.1-5%, preferably 0.5-4%.

[0055] In order to better explain the present invention, the following are examples, wherein the products and test methods used in the examples are as follows:

[0056] Biomass and nano-inorganic particles are provided by Sinopharm Shanghai Testing Group; sodium hydroxide is provided by Sinopharm Shanghai Testing Group with a purity of more than 99%; zwitterionic polymer coating agent FA367 is provided by Minquan Dongxing Mud Material Co., Ltd.; sulfonate copolymer filtrate reducer DSP-2 is provided by Shandong Deshunyuan Petroleum Technology Co., Ltd.; shale inhibitor Soltex is provided by Chevron Phillips Chemical Co., Ltd.; white oil is provided by Nanjing Rongji Chemical Co., Ltd.; high-temperature filtrate reducer Driscal-D (traditional high-temperature filtrate reducer) is provided by Chevron Phillips Chemical Co., Ltd.

[0057] In the following test example, the particle size distribution of the ultra-high temperature micro-nano plugging and fluid loss reducer was tested using the Bettersize 2000 laser particle size distribution analyzer; according to the test method of GB / T 29170-2012, the parameters of apparent viscosity and API fluid loss were tested. The API fluid loss reduction rate was calculated using the following formula:

[0058]

[0059] Wherein, η is the API filtration loss reduction rate, FL1 is the API filtration loss of the test pulp without adding micro-nano composite materials, and FL2 is the API filtration loss of the test pulp with adding micro-nano composite materials.

[0060] Example 1

[0061] (1) adding 7.5 g of starch to 100 mL of deionized water, stirring for 30 min at a stirring speed of 10,000 rpm and a temperature of 25° C. to obtain a first suspension;

[0062] (2) adding 7.5 g of nano-silicon dioxide to the first suspension, stirring for 60 min at a stirring speed of 10,000 rpm and a temperature of 25° C. to obtain a second suspension;

[0063] (3) Add 3.5 g of 2-acrylamide-2-methylpropanesulfonic acid to the second suspension, and stir for 15 min at a stirring speed of 8000 rpm and a temperature of 25° C. to obtain a suspension.

[0064] (4) 90 mL of the suspension was placed in a 100 mL tetrafluoroethylene removal tank and reacted at 200° C. for 16 h to obtain a reaction product.

[0065] (5) The reaction product was centrifuged at 80,000 rpm for 15 min to obtain a solid product, which was washed three times with deionized water, then dried at 80° C. for 24 h, and crushed to 200 mesh to obtain an ultra-high temperature micro-nano plugging and filtration reducer, which was recorded as SSL-1.

[0066] Example 2

[0067] (1) adding 10 g of glucose to 100 mL of deionized water, stirring for 30 min at a stirring speed of 10,000 rpm and a temperature of 25° C. to obtain a first suspension;

[0068] (2) adding 5 g of nano-silicon dioxide to the first suspension, stirring for 60 min at a stirring speed of 10,000 rpm and a temperature of 25° C. to obtain a second suspension;

[0069] (3) Add 3.5 g of 2-acrylamide-2-methylpropanesulfonic acid to the second suspension, and stir for 15 min at a stirring speed of 8000 rpm and a temperature of 25° C. to obtain a suspension.

[0070] (4) 90 mL of the suspension was placed in a 100 mL Teflon-free tank and reacted at 180° C. for 12 h to obtain a reaction product.

[0071] (5) The reaction product was centrifuged at 80,000 rpm for 15 min to obtain a solid product, which was washed three times with deionized water, then dried at 80° C. for 24 h, and crushed to 200 mesh to obtain an ultra-high temperature micro-nano plugging and filtration reducer, which was recorded as SSL-2.

[0072] Example 3

[0073] (1) adding 15 g of lignin to 100 mL of deionized water, stirring for 30 min at a stirring speed of 10,000 rpm and a temperature of 25° C. to obtain a first suspension;

[0074] (2) adding 10 g of nano-silicon dioxide to the first suspension, stirring for 60 min at a stirring speed of 10,000 rpm and a temperature of 25° C. to obtain a second suspension;

[0075] (3) 90 mL of the second suspension was placed in a 100 mL Teflon removal tank and reacted at 240° C. for 14 h to obtain a reaction product.

[0076] (4) The reaction product was centrifuged at 80,000 rpm for 15 min to obtain a solid product, which was washed three times with deionized water, then dried at 80° C. for 24 h, and crushed to 200 mesh to obtain an ultra-high temperature micro-nano plugging and filtration reducer, which was recorded as SSL-3.

[0077] Example 4

[0078] (1) adding 10 g of cellulose to 100 mL of deionized water, stirring for 30 min at a stirring speed of 10,000 rpm and a temperature of 25° C. to obtain a first suspension;

[0079] (2) adding 10 g of nano-silicon dioxide to the first suspension, stirring for 60 min at a stirring speed of 10,000 rpm and a temperature of 25° C. to obtain a second suspension;

[0080] (3) 90 mL of the second suspension was placed in a 100 mL tetrafluoroethylene removal tank and reacted at 220° C. for 16 h to obtain a reaction product.

[0081] (4) The reaction product was centrifuged at 80,000 rpm for 15 min to obtain a solid product, which was washed three times with deionized water, then dried at 80° C. for 24 h, and crushed to 200 mesh to obtain an ultra-high temperature micro-nano plugging and filtration reducer, which was recorded as SSL-4.

[0082] Example 5

[0083] (1) adding 15 g of hemicellulose to 100 mL of deionized water, stirring for 30 min at a stirring speed of 10,000 rpm and a temperature of 25° C. to obtain a first suspension;

[0084] (2) adding 10 g of nano-silicon dioxide to the first suspension, stirring for 60 min at a stirring speed of 10,000 rpm and a temperature of 25° C. to obtain a second suspension;

[0085] (3) 90 mL of the second suspension was placed in a 100 mL tetrafluoroethylene removal tank and reacted at 200° C. for 16 h to obtain a reaction product.

[0086] (4) The reaction product was centrifuged at 80,000 rpm for 15 min to obtain a solid product, which was washed three times with deionized water, then dried at 80° C. for 24 h, and crushed to 200 mesh to obtain an ultra-high temperature micro-nano plugging and filtration reducer, which was recorded as SSL-5.

[0087] Example 6

[0088] (1) adding 20 g of starch to 100 mL of deionized water, stirring for 30 min at a stirring speed of 10,000 rpm and a temperature of 25° C. to obtain a first suspension;

[0089] (2) adding 5 g of nano-silicon dioxide to the first suspension, stirring for 60 min at a stirring speed of 10,000 rpm and a temperature of 25° C. to obtain a second suspension;

[0090] (3) 90 mL of the second suspension was placed in a 100 mL tetrafluoroethylene removal tank and reacted at 200° C. for 12 h to obtain a reaction product.

[0091] (4) The reaction product was centrifuged at 80,000 rpm for 15 min to obtain a solid product, which was washed three times with deionized water, then dried at 80° C. for 24 h, and crushed to 200 mesh to obtain an ultra-high temperature micro-nano plugging and filtration reducer, which was recorded as SSL-6.

[0092] Test Example 1

[0093] The particle size distribution test was performed on the fluid loss reducers prepared in the above Examples 1-6. The specific process is as follows: the fluid loss reducer is prepared into a 0.1% suspension, ultrasonically dispersed for 20 minutes, and then the particle size distribution is tested using a Bettersize 2000 laser particle size distribution analyzer. The results are shown in Table 1. As can be seen from Table 1, the average particle size of the prepared fluid loss reducer is between 100-1000 nm.

[0094] Table 1 Particle size distribution of test samples

[0095] Test samples Average particle size (nm) SSL-1 103 SSL-2 238 SSL-3 459 SSL-4 591 SSL-5 783 SSL-6 998

[0096] Test Example 2

[0097] Preparation of bentonite-based slurry: 16 g of sodium-based bentonite for drilling fluid (Huawei Bentonite Co., Ltd.) was added to 400 mL of tap water, stirred at 10,000 r / min for 30 min, and then sealed and allowed to stand for 24 h to obtain a prehydrated 4% bentonite-based slurry.

[0098] 4 g of the fluid loss reducer prepared in Examples 1-6 and Driscal-D were added to 400 mL of bentonite-based slurry, respectively, and the slurry was stirred at 10,000 r / min for 20 min, and the API fluid loss of the slurry was tested;

[0099] The slurry was transferred to an aging tank, which was placed in a high-temperature roller heating furnace, heated at 220°C for 16 hours, cooled to room temperature, stirred at 10,000 r / min for 20 minutes, and then the API filtration loss of the slurry was tested and the filtration loss reduction rate was calculated. The results are shown in Table 2.

[0100] Table 2 API filtration loss and filtration loss reduction rate data of test samples

[0101]

[0102]

[0103] From the test results in Table 2, it can be seen that before hot rolling at 220°C, after adding the fluid loss reducer prepared in Examples 1-6 of the present invention to 4% bentonite-based slurry, the fluid loss reduction rate of the experimental slurry was higher than 40%, while after adding the traditional high-temperature fluid loss reducer Driscal-D, the fluid loss reduction rate of the experimental slurry was less than 30%. After hot rolling at 220°C, when the fluid loss reducer prepared in Examples 1-6 of the present invention was used, the fluid loss reduction rate of the experimental slurry was greater than 60%, which was significantly higher than that of Driscal-D. This shows that the performance of the fluid loss reducer for water-based drilling fluid prepared in Examples 1-6 of the present invention in controlling the fluid loss of bentonite-based slurry after hot rolling is significantly better than that of Driscal-D.

[0104] Combined with the experimental results of Test 1, the average particle size of the fluid loss reducer prepared in Examples 1-6 is between 100-1000 nm, and the micro-nano particles can effectively block the pores in the base slurry mud cake to form a denser mud cake, thereby effectively controlling the fluid loss of the base slurry.

[0105] Test Example 3

[0106] Bentonite-based slurry was prepared according to the method of Test Example 2, and then 1.2 g NaOH, 0.6 g FA367, 2 g DSP-2, 8 g Soltex and 12 g white oil were added to 400 mL of bentonite-based slurry in sequence to prepare drilling fluid Z1.

[0107] 4 g of the fluid loss reducer prepared in Examples 1-6 and Driscal-D were added to the drilling fluid Z1, respectively. After stirring at 10,000 r / min for 20 min, the rheological properties of the drilling fluid were tested.

[0108] The drilling fluid was placed in an aging tank, and the aging tank was placed in a high-temperature roller heating furnace. It was heated at 220°C for 16 hours, cooled to room temperature, stirred at 10,000 r / min for 10 minutes, and the API filtration loss of the drilling fluid was tested. The results are shown in Table 3.

[0109] Table 3 API filtration loss and filtration loss reduction rate data of test samples

[0110]

[0111]

[0112] It can be seen from the test results in Table 3 that after adding different types of fluid loss reducers to the drilling fluid Z1 and hot rolling at 220°C for 16 hours, the fluid loss reducers for water-based drilling fluids prepared in Examples 1-6 of the present invention have a fluid loss reduction rate of more than 32% on the drilling fluid Z1, with the highest reaching 45%, and the fluid loss control ability is better than that of Driscal-D. This shows that the fluid loss reducers for water-based drilling fluids prepared in Examples 1-6 of the present invention have good performance in controlling the fluid loss of drilling fluids at high temperatures.

[0113] In summary, the ultra-high temperature micro-nano plugging and filtration reducer for water-based drilling fluid prepared by the method provided by the present invention still has good filtration loss control ability at high temperature.

[0114] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a plugging type fluid loss reducer for high temperature drilling fluid, characterized in that: The method comprises: The biomass is first mixed with water to obtain a first suspension; performing a second mixing of the first suspension and the nano inorganic particles to obtain a second suspension; performing a hydrothermal carbonization reaction on the second suspension to obtain a first reaction product; The first reaction product is washed, dried, and crushed to obtain the fluid loss reducer.

2. The method according to claim 1, characterized in that The method further comprises: performing a third mixing of the second suspension and a sulfonic acid group-containing monomer to obtain a third suspension; Accordingly, subjecting the third suspension to a hydrothermal carbonization reaction to obtain a second reaction product; The second reaction product is washed, dried, and crushed to obtain the fluid loss reducer.

3. The method according to claim 1, characterized in that The biomass includes one or more of glucose, sucrose, fructose, xylose, starch, cellulose, hemicellulose, and lignin.

4. The method according to claim 2, characterized in that: The sulfonic acid group-containing monomer includes: 2-acrylamide-2-methylpropanesulfonic acid.

5. The method according to claim 1, characterized in that The nano inorganic particles include: nano silicon dioxide, and the particle size of the nano silicon dioxide ranges from 800 to 8000 meshes.

6. The method according to claim 1, characterized in that The dosage of the nano inorganic particles is 1.5-15g.

7. The method according to claim 1, characterized in that The mass ratio of the biomass to the nano inorganic particles is (1-8):

1.

8. The method according to claim 1, characterized in that The first mixing conditions include: temperature of 10-40° C., stirring rate of 2000-12000 rpm, and time of 5-60 min.

9. The method according to claim 1, characterized in that: The second mixing conditions include: temperature of 10-40° C., stirring rate of 2000-12000 rpm, and time of 5-60 min.

10. The method according to claim 1 or 2, characterized in that: The conditions of the hydrothermal carbonization reaction include: temperature of 150-300° C. and time of 8-48 h.

11. The method according to claim 1 or 2, characterized in that: The hydrothermal carbonization reaction is carried out in a polytetrafluoroethylene sealed tank.

12. The method according to claim 11, characterized in that The ratio of the volume of the second suspension or the third suspension to the volume of the polytetrafluoroethylene sealed tank is ≥ 50%.

13. A water-based drilling fluid obtained by the method according to any one of claims 1 to 12, characterized in that: include: Plugging fluid loss reducers, sodium hydroxide, zwitterionic polymer coatings, shale inhibitors, white oil and sulfonate copolymer fluid loss reducers used in high temperature drilling fluids.

14. The water-based drilling fluid according to claim 13, characterized in that: The mass percentage of the plugging-type fluid loss reducer used in high-temperature drilling fluid is 0.1-5%, the mass percentage of the sodium hydroxide is 0.1-0.3%, the mass percentage of the zwitterionic polymer coating agent is 0.1-0.5%, the mass percentage of the shale inhibitor is 1-3%, the mass percentage of the white oil is 1-3%, and the mass percentage of the sulfonate copolymer fluid loss reducer is 0.1-0.5%.

Citation Information

Patent Citations

  • Nano-composite filtrate reducer for high-temperature-resistant water-based drilling fluid and preparation method of nano-composite filtrate reducer

    CN116082570A

  • Binary comb-type copolymer temperature-resistant salt-resistant filtrate reducer and preparation method thereof

    CN116143966A

Cited By

  • Preparation method and application of high-temperature-resistant biomass-based shear strength improving agent for drilling fluid

    CN119775977A

  • Preparation method and application of high-temperature-resistant biomass-based fluid loss additive for drilling fluid

    CN119775977B

  • Lignin particles as well as preparation method and application thereof

    CN122145828A